Business News in the Early Modern Atlantic World
1 online resource (352 pages)
Keywords: Business News in the Early Modern Atlantic World explores the creation, dissemination, and consumption of a specific type of news, ‘business news', within early modern commercial news networks. The volume contains eleven case studies, written by scholars from a range of disciplines, which span the breadth of the early modern Atlantic from the first appearance of serial corantos in the seventeenth century to the United States' Declaration of Independence in the late eighteenth century. These expert contributions showcase the range of innovative methodological and theoretical approaches which can be used to study business news, including social network analysis, textual analysis, and qualitative methods.